Synthesis and optical properties of PbS/MnS core shell quantum dots - Zaini, Muhammad Safwan (2019)
Optical characteristics of colloidal quantum dots (QDs) are influenced by the dot size, composition and the capping molecules. This thesis focuses on the study of PbS/MnS core shell (CS) QDs where PbS serves as the core and MnS is the shell. The colloidal chemistry method was used to synthesise PbS QDs at room temperature. The growth of MnS shell by a simple ions substitution called cation exchange was successfully applied to fabricate the PbS/MnS core shell QDs in this research. This is a unique chemistry reaction which only can be occurred in chalcogenide material. This research also focuses on structural and optical properties of the PbS QDs and PbS/MnS core shell QDs. The structural properties were characterised by using High Resolution Transmission Electron Microscopy (HRTEM) and Energy Dispersive X-ray (EDX). The HRTEM results show that the average size of the PbS QDs was 6.00 ± 1.00 nm with spherical in shape. For PbS/MnS core shell QDs, its average size was enlarged to 7.00 ± 0.50 nm and 7.40 ± 0.60 nm for PbS/MnS CS 0.3 and PbS/MnS CS 0.6, respectively. The size was increased due to the growth of MnS shell after the cation exchange. Besides that, the analysis of elemental composition via EDX has confirmed the presence of MnS composition. From the spectrum, an EDX peak associated with Mn was observed at 5.9 keV. The optical properties and the behaviour of the charge carriers inside the PbS and PbS/MnS QDs were investigated by photoluminescence (PL) at different temperature (10-300 K), power excitation (10-200 mW) and exposure time (3- 40 minutes). At room temperature, the PL peak energies of PbS/MnS core shell QDs were blue shifted upon the increasing shell thickness due to strong confinement effect induced by the shell. Temperature dependent PL shows the effect on the PL peak energy, full width half maximum (FWHM) and PL intensity. In general, the PL peak energy and FWHM were monotonically increased as the temperature increased which related to the interaction of charge carriers with phonons. In contrast, the PL peak intensities were quenched as the temperature increased which associated with the excitation of carriers out of the QDs into non-radiative recombination centres. Photoenhancement phenomenon was studied by exposed the samples under illumination up to 40 minutes and we found that the PL intensity was increased over period of time due to the presence of oxygen. In power dependent PL, the integrated PL intensity (IPL) was increased with the increasing power density. From the graph of IPL as a function of power density, generally gradient of the graph was close to unity where the radiative recombination is dominant. The development of PbS/MnS core shell QDs would be useful in the future especially in the application of photovoltaic devices.